Problems Associated with Implementation of Ethno-Cultural Tourism Programs in Rural Areas of the Udmurt Republic according to Expert Evaluation - Tatiana A. Vlasova (Регионология, 2019)
Introduction. In recent years, forms of funding and state support of rural settlements have been gradually transformed due to the mechanisms of project management. The study is of relevance due to the emerging commitment of regional and municipal authorities to use domestic tourism as a source of raising funds for socio-economic development. The purpose of the article is to reveal regional factors in the effective implementation of tourism programs in the context of coordinating the interests of cultural institutions and authorities.